INTERNALISASI FIKIH WANITA MELALUI PEMBELAJARAN KITAB FATHUL QARIB KARYA SYEIKH IBNU QASIM AL GHAZY DI PONDOK PESANTREN AL AKROM PUTRI BANYUURIP MARGOREJO PATI - Nur Jannatin Ni’mah; Shofria Ihda Mahayyun (Almarhalah: Jurnal Pendidikan Islam, 2025)
This study aims to describe the process and outcomes of internalizing women’s fiqh among female students (santriwati) at Pondok Pesantren Al Akrom through the learning of the Fathul Qarib text authored by Shaykh Ibn Qasim Al-Ghazy. The main issue examined is how the values of women’s fiqh are internalized through learning activities within the pesantren environment, which is characterized by a distinctive educational tradition rooted in classical Islamic scholarship. This research employs a qualitative approach, with data collected through observation, in-depth interviews, documentation, and triangulation to ensure data validity. The data were analyzed descriptively through three stages: data reduction, data display, and conclusion drawing. The findings reveal that the internalization of women’s fiqh is carried out systematically through three main stages—planning, implementation, and evaluation of learning—each aimed at fostering both conceptual understanding and practical application of women’s fiqh principles in daily life. The process results in three learning dimensions: knowing (understanding the principles of women’s fiqh), doing (applying those values in everyday practice), and being (embodying them as part of the students’ religious character). One concrete outcome of this process is the creation and use of a menstrual calendar as a reflective and practical learning tool. Overall, the learning of women’s fiqh through the Fathul Qarib text provides a meaningful and profound contribution to strengthening religious knowledge, spiritual awareness, and the formation of Islamic identity among female students in the pesantren.